2005
DOI: 10.1590/s0101-20612005000200009
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetro bromatológicos de grãos crus e torrados de cultivares de café(Coffea arabica L.)

Abstract: RESUMOO objetivo deste trabalho foi determinar o teor de sólidos solúveis e medir a acidez total e o pH de grãos crus e torrados de oito cultivares mais plantadas na região Sul de Minas Gerais, assim como verificar a influência da torração nestes parâmetros. Para tal, frutos das cultivares Mundo Novo, Topázio, Catuaí Vermelho, Catuaí Amarelo, Acaiá Cerrado, Rubi, Icatu Amarelo e Icatu Amarelo foram colhidos na Fazenda Experimental de São Sebastião do Paraíso, da Empresa de Pesquisa Agropecuária de Minas Gerais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
2
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 0 publications
2
12
2
7
Order By: Relevance
“…The result found for the cultivar New World 19/474 (30%) is close to that observed by Fernandes et al (2003) who analyzed chemical constituents and content of aqueous extracts of roasted Arabica (Coffea arabica) and conilon coffees (Coffea conilon), and achieved 31.39% of total soluble solids. Results of Mendonça et al (2005) differ from our results (10.0-37.5%), probably due to the form of roasting the beans.…”
Section: Total Soluble Solidscontrasting
confidence: 99%
“…The result found for the cultivar New World 19/474 (30%) is close to that observed by Fernandes et al (2003) who analyzed chemical constituents and content of aqueous extracts of roasted Arabica (Coffea arabica) and conilon coffees (Coffea conilon), and achieved 31.39% of total soluble solids. Results of Mendonça et al (2005) differ from our results (10.0-37.5%), probably due to the form of roasting the beans.…”
Section: Total Soluble Solidscontrasting
confidence: 99%
“…canephora accessions from the Conilon and Robusta botanical varieties represent important sources of variability for development of new varieties with differentiated beverage quality (ROCHA;VENEZIANO, 1993) since each botanical variety has different amounts of soluble solids, which influence the body, aroma, acidity, and astringency of the beverage (ESQUIVEL; JIMÉNEZ, 2012;MENDONÇA, PEREIRA;MENDES, 2005). In Rondônia, Veneziano (1993) evaluated the quality of coffee from seven accessions of Conilon and…”
Section: Samplesmentioning
confidence: 99%
“…Fernandes et al (2003) obtained values of 26.97 °Brix and 28.17 °Brix for Arabica coffee and 31.39 °Brix for Robusta coffee with medium roasting. Mendonça et al (2005) found a range from 23.77 to 27.89 °Brix for eight genotypes of Arabica coffee submitted to light roasting.…”
Section: Malaquias J V Et Almentioning
confidence: 92%